Influence of Spaying Parameters on the Property of Detonation Coatings Based on Ta - D.N. Kakimzhanov; Z.A. Satbayeva; M.K. Dautbekov; Y.S. Turabekov; R.M. Kuanyshbay; A.S. Rustemov (Қарағанды университетінің хабаршысы. Физика сериясы)
This paper investigates the influence of sputtering parameters on the properties of tantalum-based detonation coatings. One of the key parameters in sputtering is the volume of barrel filling, which affects the properties of the resulting coatings. Tantalum coatings were produced at various levels of barrel filling with explosive gas, specifically at 50–70% fill levels. The results demonstrated that the roughness of the coatings decreases as the barrel fill volume increases, leading to coatings with a more homogeneous structure. Additionally, the tests revealed that coatings produced at 60% fill exhibited superior corrosion resistance compared to the other samples. Based on these findings, the optimal barrel fill level for explosive gas was determined.